Evaluasi Sistem Pengendalian Internal Penerimaan Kas pada Apotek Kimia Farma 307 Banyuwangi - Vicky Roh Idhofi; S. Sudarno; Agung Budi S. (UPT Penerbitan Universitas Jember, 2018)
Internal control system in a company is one form of action used to safeguard property owned by the company. The existence of an internal control system is expected to prevent the risk of errors occurring either intentional or without the element of intent. The risk of such errors can be derived from the various parties concerned. This is one reason that good procurement control system in an accounting system in this case is in the system of cash receipts. From the observation while at Kimia Farma 307 Banyuwangi seen that in a system of cash receipts from cash income services namely health checks and cash sales are still very modest. The accounting system of the cash receipts of the business activity is only using the document pickup. When viewed from the frequency of sales and service checks every day, the system that has been used is deemed to be less effective in terms of internal controls. This study aims to determine in real terms how the internal control system of cash receipts and evaluation of internal control systems at these pharmacies. This research uses qualitative method to analyze the data. The data obtained from three data collection methods are interview, observation and documentation. Keywords: system of internal control, cash receipts in cash, accounting system, system evaluation